The Importance of Task-Based Approach in Language Learning - G’ofurova Shohsanam (Zien Journals, 2022)
This article deals with the problems of innovative ways of teaching English. It studies the importance of task-based approach and characteristic features of thich teaching method.
Keywords: contemporary methods; Validity; acquisition; productive or receptive skills